Validitas konten penapisan mandiri malagizi pada aplikasi “IDAMAN GIZI” - Susiyana, Nadia; Andrestian, Meilla Dwi; Syainah, Ermina; Dewi, Zulfiana (Poltekkes Kemenkes Aceh, 2026)
Background: Malnutrition is a complex condition involving interactions between underlying diseases, metabolic alterations, and inadequate nutritional intake, thereby requiring early management to prevent health deterioration. The self-screening tool in the “IDAMAN GIZI” application improves the early detection of malnutrition risk, reduces the burden on healthcare workers, and empowers patients.”.Objectives: This study assessed the validity of a self-screening instrument for malnutrition implemented within the “IDAMAN GIZI” mobile application for outpatients at RSD Idaman Banjarbaru City, Indonesia.Methods: This study used the CVI assessed by four media and four subject matter experts, along with the face validity index (FVI) by ten respondents. The study was conducted at RSD Idaman Banjarbaru from August to December 2025. Quantitative data from the assessment questionnaires were analyzed using the item content validity index (I-CVI), scale content validity index (S-CVI), and Cohen’s kappa reliability test. Qualitative data in the form of comments and suggestions were thematically analyzed to improve the instrument.Results: Based on the assessment by experts, the I-CVI, S-CVI, and overall content validity index (CVI) scores were all 1. Furthermore, the FVI scores provided by the respondents were I-FVI before (P0) = 1 and I-FVI after (P1) = 1, with S-FVI/Ave = 0.99 and S-FVI/UA = 0.86.Conclusion: The validity assessment of the “IDAMAN GIZI” self-screening instrument indicates that it is valid for wide-scale implementation. Further research is warranted to develop secure data storage features, a monitoring dashboard for nutrition professionals, and integration with national health programs to enhance the detection of regional malnutrition.